Gamma Radiation Effects on some Growth Patterns in Hedge Lucerne (Desmanthus virgatus L.) - Ameena Premnath, A. Kalamani, C.Babu and G. VijayaKumar (Electronic Journal of Plant Breeding, 2010)
Seeds of Hedge lucerne (Desmanthus virgatus) were exposed to different doses (50 to 500 Gys, with an interval of 50 Gys)of gamma rays (Cobalt-60) to determine the effectiveness of different doses on growth behaviour and biomasscharacteristics. The lethal dose (LD50) was found to be 250 Gys. About thirty five mutants were identified. High biomassyielding dwarf statured plants were identified from the treatments of 350 and 500 Gys irradiation. Similarly high fodderyielding superior plants as a result of increased number of branches ranging from 22-34 were observed in 400 and 450 Gyspopulation when compared to the control (12-16 branches). Plants of bushy stature with shorter intenodal length (2.25 cm)when compared to control (3.75 cm) were found among the 450 Gys population. Prostrate types were also identified amongthe 50, 350, 400 and 500 Gys population suited for grazing pastures. Based on single plant performance, plants which recordhigh biomass will be identified and M1 seeds will be collected and studied in further generations.